Effect of adding salvia officinalis oil to the ration in some blood traits of broiler ross 308 - Alsaadi, Sarmad Abdul Razak; Alnidawi, Nihad Abdel Latif Ali (Journal of Kerbala for Agricultural Sciences, 2017)
This study becomes conducted to analyze the impact of supplementing sage oil to the ration of Ross 308 chicks on some hematological parameters. 117 broiler chicks are used at one day old were randomly occupied to three treatments (by 3 replicates per treatment; 13 chicks per replicate), and treatments were as follows: Control group: without adding Salvia officinalis to the diet, First treatment group: adds Salvia officinalis by 1% and Second treatment group: add Salvia officinalis by 2%. The experiment included a study of the following hematological parameters: Red Blood Corpuscular Count, Packed Cell Volume, Estimation of Hemoglobin and Differential Leukocytes Count. The results improved that the addition of Salvia officinalis by 1 and 2% to broiler diet led to a significant increment (p<0.05) in RBCs count, PCV, and Hb concentration. From other hand, significant decreasing (p<0.05) in H/L Ratio. The ameliorating that happens in chicks hematological traits attribute to be added Salvia officinalis their ration .